Hubungan Job Insecurity dan Job Satisfaction pada Karyawan Outsourcing di PT.X - Subur Triyono; Indra Wahyudi; Dewi Handayani Harahap (LPPM Universitas Proklamasi 45, 2020)
The emergence of outsourcing systems makes workers experience job insecurity in their work. This condition is due to the many policies that are biased by the workers especially related to the continuity of work in the future, because the companies can just do layoffs at in any time. so that this sense of security is very influential on job satisfaction of these employees.This study aims to determine empirically whether there is a relationship between job insecurity with job satisfaction among outsourced employees at PT.X. This research uses quantitative research methods with data collection using scale. The subjects in this study were PT.X employees with outsourcing employees who had worked for six months and had signed a work contract. The data analysis technique used is the Pearson product moment correlation technique.The results showed that the correlation coefficient rxy = -0.128 with p = 0.326 (p> 0.01). This means that between job insecurity and job satisfaction is not proven to have a significant relationship with outsourcing employees at PT.X.The conclusion of this study is that there is no significant relationship between job insecurity with job satisfaction among outsourcing employees at PT.X, this shows that there are other another factors of job insecurity that have a greater role to do with job satisfaction.